Professional Competence of Madrasah Ibtidaiyah Teachers: A Didactical Design Research Study - Dwi Warli; Didi Suryadi; Siti Fatimah; Suhendra Suhendra (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2025)
The professional competence of Madrasah Ibtidaiyah (MI) teachers in teaching ratio material is a vital factor in improving students’ understanding of mathematics, making it important to examine MI teachers’ knowledge of mathematics content. This study aims to analyze teachers’ professional skills, including their understanding of the concept of ratios, their attitudes toward preparing the learning process, such as creating teaching materials aligned with the curriculum, and their understanding of students’ characteristics and how they design learning. The results of this study provide an initial foundation for further research, which can help teachers develop learning methods through didactic studies. The subjects of this research are MI grade VI teachers in Bandung Regency, from six schools. The method used is a descriptive approach with a prospective analysis stage based on Didactical Design Research (DDR). Data collection involved teacher reflection sheets, exploratory interviews, observations, and document reviews. The findings indicate that teachers’ professional competence in knowledge of learning content and teaching methods remains at level 2, while their understanding of students’ characteristics and learning styles is at level 3. Reflection sheets and interviews reveal that teachers face difficulties beginning with defining ratios, particularly in understanding that the ratio of a to b differs from the ratio of b to a, and in solving problems involving equal proportions. Often, teachers plan their lessons with a simple sequence of materials in a journal, without considering the epistemic and systemic aspects of the content or validating their presentation and practice questions found in textbooks. MI teachers also find it challenging to select concrete teaching methods for ratios before moving to an abstract understanding, especially given the limited time. Based on these findings, there is a clear need for programs to improve teachers’ competence through didactic studies, equipping them to anticipate and address potential obstacles and enabling them to design compelling learning experiences. Since teachers’ professional competence in teaching ratios directly impacts students’ understanding of math, exploring their content knowledge is essential. This study contributes to empowering teachers through didactic design research, a necessary approach to enhancing teacher competence.